Ultra-weak photon emission during wrist curl and cycling exercises in trained healthy men - Seo, Dong-II; M. Laager, Frédéric; Young, Kaelin; Chang, Hyukki; So, Wi-Young; Kim, Hee-Tae; Soh, Kwang-Sup; Song, Wook (Electromagnetic biology and medicine, 2012)
Human ultra-weak photon emission (UPE) is related to the activity of respiratory chain and oxygen consumption. Investigations on UPE and its response to exercise are almost non existent. Since human UPE is an indicator of reactive oxygen species (ROS) levels, we used exercises as a model to study UPE. To continue the research on the relationship between human UPE and exercise, it was decided to carry out measurements of UPE in response to different exercise modes with 20 healthy male subjects. The performed exercises were wrist curls with a dumbbell and indoor cycling. Regarding wrist curl exercises, 70% of the subjects for the first exercise and 65% for the second exercise did not show any significant changes in UPE. Also, the statistical analysis did not show significant changes of the UPE levels. In terms of cycling exercise, 85% of subjects did not show any significant increase of UPE. The gathered data showed that a majority of the subjects didn't show an increase of the UPE during both types of exercises. Our results imply that the UPE is not only affected by oxygen consumption, but also by the intensity, the type of exercise, and the physiology of the subject.